Geometry and structure of the pull-apart basins developed along the western South American-Scotia plate boundary (SW Atlantic Ocean) - Esteban, Federico Damián (2018)
The South American-Scotia plate boundary is a left-lateral fault system which runs roughly E-Wfor  m o reth an  3000 km across the SW Atlantic Ocean and the Tierra del Fuego Island, reaching to the west thesouthern Chile Trench. Analyses of a large dataset of single- and multi-channel seismic reflection profiles acquired offshore has allowed to map the trace of the plate boundary from Tierra del Fuego to the Malvinas Trough, a tectonic depression located in the eastern part of the fault system, and to reconstructt he shape and geometry of the basins formed along the principal displacement zone of the fault system. Three main Neogene pull-apart basins that range from 70 to 100 km in length, and from 12 to 22 km inwidth, have been identified along this segment of the plate boundary. These basins have elongated shapes with their major axes parallel to the ENE-WSW direction of the fault zone. The sedimentary architecture and the infill geometry of the basins suggest that they represent mostly strike-slip dominated transtension basins which propagated from E to W. The basins imaged by seismic data show in some cases geometrical and structural features linked to the possible reactivation of previous wedge-top basins and inherited structures pertaining to the external front of the Magallanes fold-and-thrust compression belt, along which the South American-Scotia fault system has been superimposed. It is sugge sted that the sequence of the elongated basins occur symmetrically to a thorough going strike-slip fault, in a left-stepping geometrical arrangement, in a manner similar to those basins seen in other transcurrent environments.